Experimental Validation of an In Vitro Method for Assessing Insulin-Dependent Glucose Uptake - A. N. Afanasyeva; V. B. Saparova; I. E. Makarenko; R. V. Drai; T. A. Selmenskikh (Регуляторные исследования и экспертиза лекарственных средств)
Russian and international regulatory documents require that analytical procedures for establishing bioequivalence and comparability of quality attributes of biotechnological (biological) products, carrying out batch release of medicinal products, and conducting other equally  important in  vitro  studies must be  validated. These in vitro studies include molecule–receptor binding and product bioactivity assays. However, at present, there is no single approach to validation of in vitro bioanalytical methods not involving the determination of active ingredient concentrations in biological fluids. The aim of the work was to validate a procedure for assessing insulin-dependent glucose uptake and demonstrate the suitability of GOD-PAP GLUCOSE kits for glucose determination in culture media. Materials and methods: The study used RinFast® insulin aspart by Geropharm, Russia; a placebo for insulin aspart; the L6J1 rat myogenic cell line; and a GOD-PAP GLUCOSE kit for quantitative determination of glucose. The study was carried out on differentiated cells cultured for 7 days. To encourage L6J1 differentiation, the authors used DMEM with 4.5 g/L glucose and 2% horse serum. The statistical analysis of results was performed using Prism 9. Results: The study demonstrated the analytical procedure’s specificity, as the concentration of residual glucose in the culture medium observed with the placebo was 4 times higher than that with the maximum concentration of the medicinal product. The determination of precision showed the repeatability of 4–9% and the intralaboratory precision of 11–16%. The coefficient of variation for robustness amounted to 14% in 4 independent experiments comprising a total of 9 analytical runs. The authors compared insulin products (the insulin aspart and a genetically engineered human  insulin),  and the half-maximal inhibitory concentration (IC50) values differed by 1.5 times. For the GOD-PAP GLUCOSE kit, the linear regression coefficient  of  determination was 0.9983, the sensitivity amounted to 1 mmol/ L, and the accuracy ranged between 95% and 107%. Conclusions: the procedure using L6J1 rat myoblasts as  a test system may be considered specific, highly precise, and robust in assessing insulin-dependent glucose uptake and suitable for detecting biological activity   of insulin preparations in vitro.